Covered vs Uncovered Stents for Aortoiliac and Femoropopliteal Arterial Disease: A Systematic Review and Meta-analysis. (June 2016) - Hajibandeh, Shahab; Hajibandeh, Shahin; Antoniou, Stavros A.; Torella, Francesco; Antoniou, George A.
Purpose: To evaluate outcomes of covered vs bare metal stents for the treatment of lower limb peripheral artery disease.Methods: A search of electronic databases was performed to identify all studies comparing outcomes of covered vs bare metal stents for treatment of aortoiliac and femoropopliteal arterial disease. The Cochrane tool and the Newcastle-Ottawa scale were used to assess the risk of bias in randomized controlled trials (RCTs) and observational studies, respectively. Fixed or random effects models were applied to analyze pooled outcome data. The results for dichotomous outcome variables are presented as the odds ratio (OR) and 95% confidence interval (CI); intergroup comparisons of continuous clinical variables are reported as the mean difference (MD) and 95% CI.Results: Two RCTs and 4 retrospective cohort studies, enrolling 744 patients (mean age 67 years; 477 men) and 918 diseased arteries, were identified. For aortoiliac disease, treatment with a covered stent showed no significant improvement in primary patency (OR 2.10, 95% CI 0.48 to 9.11, p=0.32), but it was associated with higher ankle-brachial index (ABI) (MD 0.08, 95% CI 0.07 to 0.09, p<0.001) and a lower reintervention rate (OR 0.19, 95% CI 0.09 to 0.42, p<0.001). For femoropopliteal disease, use of covered stents was associated with increased primary patency (OR 1.84, 95% CI 1.11 to 3.06, p=0.02), higher ABI (MD 0.08, 95% CI 0.00 to 0.16, p=0.04), and a lower reintervention rate (OR 0.51, 95% CI 0.30 to 0.87, p=0.01). No significant differences in technical success, complications, limb salvage, or survival were identified between the groups in either segment.Conclusion: Theoretically, the use of covered stents may increase the patency rate due to decreased restenosis after stent placement. This analysis found that the primary patency was improved with the use of a covered stent in femoropopliteal lesions but not in aortoiliac disease. Improved outcomes were seen with covered stents compared with bare metal stents as indicated by a lower need for reintervention and an improved ABI. It remains to be investigated whether such beneficial effects can be translated into improved clinical outcomes, such as limb salvage and amputation-free survival. Long-term results of the comparative efficacy of covered stents over bare metal stents are not currently available.